PENGEMBANGAN MODUL TERAPI AL-QUR’AN SURAT AL-INSYIRAH AYAT 1-8 UNTUK MENURUNKAN TINGKAT STRES SANTRI PONDOK PESANTREN DARUL HIKMAH PEKANBARU - Rizki Indah Lestari; Zulfan Saam; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : This study determines to develop a therapy module of Al-Qur'an Surah Al-Insyirah Verses 1-8 to reduce the students' stress levels. The type of this study is Research and Development (R&D) level 1 as the lowest level of development by conducting research but not continuing with field testing. In developing a better module, this research carried out a validation test for two areas of expertise, which are material experts and interpreters. The data collection techniques in this study used interviews and validation questionnaires. The result of this research is that the compiled module of Al-Qur'an Surah Al-Insyirah Verse 1-8 therapy to reduce the stress level of students divided into five guidance activities with a total reading duration of ± 40 minutes. The result of the module validation test as a whole based on the material and interpretation aspects shows that the assessment obtained an average value of 84.4% declared "Eligible" to be tested as a learning media.Key Words: Module, Therapy of the Qur'an Surah Al-Insyirah, Reducing Stress Levels